Fluorescence, Decay Time, and Structural Change of Laser Dye Cresyl Violet in Solution due to Microwave Irradiation at GSM 900/1800 Mobile Phone Frequencies - Fuat Bayrakceken; Korkut Yegin (International Journal of Photoenergy)
Microwave irradiation at GSM 900/1800 MHz mobile phone frequencies affects the electronic structure of cresyl violet in solution. These changes are important because laser-dye cresyl violet strongly bonds to DNA- and RNA-rich cell compounds in nerve tissues. The irradiation effects on the electronic structure of cresyl violet and its fluorescence data were all obtained experimentally at room temperature. For most laser dyes, this is not a trivial task because laser dye molecules possess a relatively complex structure. They usually consist of an extended system of conjugated double or aromatic π-bonds with attached auxochromic (electron donating) groups shifting the absorption band further towards longer wavelength. Because of the intrinsically high degree of conjugation, the vibrational modes of the molecular units couple strongly with each other. We found that the fluorescence quantum yield was increased from to due to intramolecular energy hopping of cresyl violet in solution which is exposed to microwave irradiation at mobile phone frequencies, and the photonic product cannot be used as a laser dye anymore.